A New Formulation of University Loss by Taking into Account Hidden Loss - JAFARI , Bouchra; YOUSFI , Abdellah (Revue Internationale des Sciences de Gestion, 2022)
Being alone, dismayingly overwhelmed by a deficit spending situation is the case of Moroccan universities that have marked the seal of budgetary mismanagement suffering from financial handicaps in chain to the point of becoming impassable. There is no doubt that university loss (also called Input-output ratio) is one of the main reasons why financial resources are insufficient to cover all university needs. However, if there is a criticism to be made, it would be that the university loss as an indicator is miscalculated, since it unintentionally leaves out of its formula the hidden costs due to the absenteeism of teacher-researchers and students, who are considered as an imperceptible financial abyss. Therefore, revisiting the formula of university loss is a challenge because it is a problem that has rarely been addressed in depth, and we will attempt to provide a detailed analysis of this problem by linking university loss to the hidden costs related to the absenteeism of teacher-researchers and students. To put it simply, the objective of this article is to correct the indicator of university loss, so that the university financial system, which is hit by a double penalty of both direct and indirect costs, can stay afloat.